Tata Kelola Pelaksanaan Lelang Eksekusi Pajak Di Kantor Pelayanan Kekayaan Negara Dan Lelang Jakarta III Sebagai Upaya Penagihan Pajak - Selvi Selvi; Notika Rahmi; Maya Puspita Dewi; Muhammad Ihram (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to analyze the governance and problems of the tax execution auction in Jakarta III State Property Office and Auction as tax collection effort. This is related to the sale realization of the tax execution object which is always lower than the actual value of the object for confiscation. This study uses a qualitative approach with data collection techniques through interviews, observation and use of secondary data. The results showed that the governance of auction basically has met the principles of transparency, accountability, and good coordination. However, the problem lies in the low community participation. This is due to the biased rules for auction announcements as well as too high a limit on the auction object value. In addition, the efficiency of auction implementation is also considered to be less good in terms of time and material.